Caring and technology in an intensive care unit: an ethnographic study. Issue 6 (10th July 2013) - Price, Ann M
ABSTRACT: Background: Critical care practice is a mixture of caring and technological activities. There is debate about whether the balance between these two elements is correct and a concern that critical care units can dehumanize the patient. This research sought to examine aspects that might affect this balance between the caring and technology within the critical care setting. Aim: What aspects affect registered health care professionals' ability to care for patients within the technological environment of a critical care unit? Methodology: A qualitative approach using ethnography was utilized as this methodology focuses on the cultural elements within a situation. Data collection involved participant observation, document review and semi‐structured interviews to triangulate methods as this aids rigour for this approach. A purposeful sample to examine registered health care professionals currently working within the study area was used. A total of 19 participants took part in the study; 8 nurses were observed and 16 health care professionals were interviewed, including nurses, a doctor and 2 physiotherapists. The study took place on a District General Hospital intensive care unit and ethical approval was gained. Findings: An overarching theme of the 'Crafting process' was developed with sub themes of 'vigilance', 'focus of attention, 'being present' and 'expectations' with the ultimate goal of achieving the best interests for the individual patient. Conclusion: The areas reflected in this study coincide with the care, compassion, competency, commitment, communication and courage ideas detailed by the Department of Health (2012). Thus, further research to detail more specifically how these areas are measured within critical care may be useful. Relevance to practice: Caring is a complex concept that is difficult to outline but this article can inform practitioners about the aspects that help and hinder caring in the technical setting to inform training.